A sense of legitimacy in low-impact developments: experiences and perspectives of communities in South-West England. Issue 1 (2nd January 2022) - Griffin, Emma; McClymont, Katie; Sheppard, Adam
Abstract: Informality in the global North has been largely overlooked in literature to date (Devlin, 2018 ). Unlike the global South, the role of informal practices in northern countries are under-represented in both theory and practice. Despite this, informality has a long and established role in housing provision outside of the global South. However, contradictions in what is perceived as legitimate and illicit or unlawful, compounds barriers between planners, policy makers and people living in informal ways. This article draws on a two-year research project that engaged with people living informally to better understand their relationship with the planning system. Grounded in real life experiences, this article engages with questions around how and if informality could be better supported in planning policy, as a space for innovative, flexible and adaptive approaches to housing production. In so doing, it challenges the way housing is conceptualised in most mainstream global North policy and academic discourse. Finally, the article sets out how informality in the highly regulated English countryside provides a useful lens through which to develop a more nuanced debate on the role of informality in wider planning practice.